THE ROLE OF HIGH-TECH MEDICAL CARE IN THE HEALTH CARE SYSTEM (REVIEW ARTICLE) - Rizaev Jasur Alimzhanovich; Saidov Maksud Arifovich; Farida Odylovna Khasanjanova (Scholar Express Journals, 2023)
This review article analyzes the role of high-tech medical care (HCT) worldwide, including in Uzbekistan. It also examines the tasks for reducing mortality, morbidity and disability from CVD to the state cardiology services
Keywords: High technology medical care; cardiovascular diseases; mortality; morbidity and others